(untitled) (Bangladesh Journal of Agricultural Research, 2016)
A study was conducted during 2012-13 to build union level digital databases and maps of maize growing areas using both primary and secondary data. Primary data were collected from maize growing areas of the upazilla namely Pirgonj of Thakurgaon district. For summer and winter maize; union, upazila, district and country level digitized maps were used in the study. Geographical Information System (GIS), Global Positioning System (GPS) and Management Information System (MIS) related Information Technology (IT) were also applied. Total cultivable land 28138 ha in Pirgonj upazila and area and production of maize were 5100 ha and 34508.75 t respectively. Sixteen (16) varieties were cultivated in the study areas and maximum area (74.09%) of maize was cultivated by the executive varieties NK40, Pacific 984, 900M Gold, 900M, 3396, and Supergold. Average maize yield of the study areas was 6.77 t/ha during 2012-13. A web site was developed for variety wise area coverage data collection of maize as well as for other crops. This web site can also be used in mobile phone. Bangladesh J. Agril. Res. 40(4): 693-702, December 2015